Analisis Peraturan Pejabat Pembuat Akta Tanah (PPAT) Perspektif Kepastian Hukum di Indonesia - Al-Asyari, Shella Virgina Umma; Yunanto, Yunanto (Universitas Muhammadiyah Ponorogo, 2025)
This research is motivated by the importance of the role of Land Deed Officials (PPAT) in the land law system in Indonesia which requires high standards of integrity and professionalism. The problems that arise in the regulation of temporary dismissal of PPAT due to violations, the absence of clear boundaries, resulting in legal uncertainty. The purpose of this study is to analyze the regulation of temporary dismissal of PPAT due to violations, in order to realize legal certainty in Indonesia. The formulation of the problem of this research is to what extent the regulation of temporary dismissal of PPAT due to disgraceful acts has fulfilled the principle of legal certainty. The research method used is normative juridical, with a statutory approach, analysis of various relevant legal literature. The results of the study indicate that the regulation regarding violations that can result in temporary dismissal of PPAT needs to be given clear boundaries. Ensuring that these regulations are in line with the applicable principle of legal certainty, as applied to other public offices in Indonesia. The existence of clear boundaries is expected to create clarity in the application of the law, thus providing adequate legal protection for PPAT in carrying out their duties.